Chemometrics study and assessment of selected Indian dishes in Taman Universiti Teknologi Malaysia for sourcing essential mineral nutrients - Salau, Rasaq Bolakale (2014)
Purpose of food is primarily to maintain life based on the inherent nutritive and nourishment properties of its content. This study is aimed at examining the mineral content of table ready dishes as remedy for a number of Mineral Deficiency Diseases (MDD). It is a more convenient alternative to conventional supplementation which is less affordable and sometimes harmful. Food samples were collected as served dishes from local restaurants around Taman Universiti Teknologi Malaysia. The dried samples were blended in electric blender made of plastic chamber and stainless steel blade. Optimum wet ashing procedure was adopted with control of heat and proportionate use of Nitric acid and Hydrogen Peroxide. The elements (Ca, Mg, K and Na) were obtained using Flame Atomic Absorption Spectrometry (FAAS). Phosphorus was determined using Inductively Coupled Plasma- Mass spectrometry (ICP-MS).The studied dishes revealed the presence of these elements but in varied quantities. Unsupervised techniques of the Principal Component Analysis (PCA) and Cluster Analysis (CA) were employed to distinguish patterns and groupings among the dishes. The PCA revealed a reduced dimension of the whole variables into two Principal Components responsible for 90% of the total variability. Both PCA scores and CA dendrogram show one large grouping and sets of some independent food samples. While Banana leaf rice and Roti canai stand out, the other interesting set consisting of Banana Leaf rice, Fish head curry and Nasi Beriani highly correlate positively with Ca, Na, P and K elements. Overall result shows that the Required Dietary Allowance (RDA) for the mineral elements can be met with careful choice of food, hence being, potential remedies for some MDDs.